Glucosinolates in non-Brassicales plant species: critical literature evaluation and testing of two high chemical quality reports - Đulović, Azra; Koch, Marcus; Thongyoo, Panumart; Pattison, David I.; Blažević, Ivica; Rollin, Patrick; Agerbirk, Niels (Biochemical systematics and ecology, 2024)
Glucosinolates (GSLs) are secondary metabolites mainly found in the plant order Brassicales. We critically evaluate reports of GSLs in other orders of flowering plants, propose standards for future reports and subject two cases to rigorous testing. Reports of GSLs in non-Brassicales species should live up to state-of-the-art scientific standards concerning chemical evidence, botanical evidence and biological replication. Occurrence of GSLs in the family Putranjivaceae, order Malpighiales (genera Putranjiva and Drypetes) was reasonably supported, but state-of-the-art confirmation was required. Hence, the taxonomic identity of Putranjiva roxbughii seeds with the previously known GSL profile was confirmed using DNA-based methods. Similarly, good suggestive evidence exist from the family Violaceae, order Malpighiales, but in need of confirmation. No other report of any GSL in a non-Brassicales species meet the proposed scientific standards, but suggestive evidence exists for the family Phytolaccaceae, order Caryophyllales and to a lesser extent family Celastraceae, order Celastrales. A recent report of a GSL in a tropical plant suggested to be a species in the order Sapindales was subjected to a rigorous testing in terms of chemical analysis, biological replication and botanical identification including DNA sequencing. We confirmed the original report concerning chemical structure and reproducibility but revised the botanical identification to a species from the Brassicales order (family Capparidaceae). Hence this paper also reports myrosinase activity, isothiocyanate-type GSL products from roots and stems, and GSL profile of roots, stems, leaves and fruits of Capparis sepiaria L., dominated by Leu-derived 2-methylpropyl GSL in vegetative parts, Val-derived 1-methylethyl GSL and Ile-derived 1-methylpropyl GSL in fruits, and additionally Trp-derived indol-3-ylmethyl GSL and 4-hydroxyindol-3-ylmethyl GSL in immature fruits. Several other GSLs were searched for and conclusively not found above the limit of detection.